Conformations of large macrocycles and ring-in-ring complexes. Issue 6 (23rd March 2016) - Klosterman, Jeremy K.; Veliks, Janis; Frantz, Derik K.; Yasui, Yoshizumi; Loepfe, Michael; Zysman-Colman, Eli; Linden, Anthony; Siegel, Jay S.
Abstract : A kinetically directed, stepwise approach towards molecular Borromean links enabled the isolation and structural characterization of synthetic intermediates along the way. Abstract : A kinetically directed, stepwise approach towards molecular Borromean links enabled the isolation and structural characterization of synthetic intermediates along the way. Here we report the synthesis and crystal structures of three flexible macrocyclic intermediates and a new ring-in-ring complex, anchored together through ruthenium(ii ) centers, which contains open terpyridine caps in the inner Ring II. Terpyridines circumvent the conformational cis / trans limitations of bipyridines and the new ring-in-ring complex forms tetrametallic complexes with Zn(ii ), Pt(ii ) and Ru(iii ) metal ions. Analysis of the four macrocyclic structures provides a good foundation for the conformational flexibility in these complexes and demonstrates the robust applicability of the terpyridine design elements towards the engineered synthesis of ring-in-ring topologies.